An exploratory factor analysis of health professional perceptions of integrating spirituality in daily patient care - Yahya, Fatimah; Hassan, Hafizah Che; Panduragan, Santhna Letchmi; Mat, Samsiah; Mohd Said, Faridah (YCAB Publisher, 2024)
Introduction: Spirituality is very subjective, and it is commonly assumed as the modifiable factors that can affect the quality of life among elderly, where elderly is referred to the male or female with the age of above 60 years old. The main purpose of this study is to evaluate the perception of nurses toward spirituality in nursing care practice among the patients. Methods: An exploratory sequential design using qualitative study [N=24] by collecting data via face-to-face interview in Federal Territory of Kuala Lumpur. The spirituality tool was analysed using four categories: 1) Believe, 2) Faith, 3) Emotion and 4) Practice. Results: The reliability of the dimensions was all high as the Cronbach’s Alpha coefficients were above 0.90. Therefore, this spirituality measurement tool can be considered highly reliable. It was found, there was significant relationship between age, ethnicity, religion, versus the four-spiritual dimension. However, the results showed that there is no relationship between gender and spirituality dimension. Conclusion: In conclusion spirituality play large role throughout the individual and variances of cultural and closely context toward nursing. The spiritual care encompasses beliefs that significantly give meaning to the life of an individual, and then able to motivate individuals where may enhance the faith, hope, peace, and empowerment to an individual health. It was used to construct a profile of elderly in Malaysia, and it may be applied to profile elderly in other countries.